Discovery of rare protein‐coding genes in model methylotroph Methylobacterium extorquens AM1. Issue 23 (2nd October 2014) - Kumar, Dhirendra; Mondal, Anupam Kumar; Yadav, Amit Kumar; Dash, Debasis; Pandey, Akhilesh; Pevzner, Pavel A.
<x xml:space="preserve">Abstract</x> Proteogenomics involves the use of MS to refine annotation of protein‐coding genes and discover genes in a genome. We carried out comprehensive proteogenomic analysis of Methylobacterium extorquens AM1 (ME‐AM1) from publicly available proteomics data with a motive to improve annotation for methylotrophs; organisms capable of surviving in reduced carbon compounds such as methanol. Besides identifying 2482(50%) proteins, 29 new genes were discovered and 66 annotated gene models were revised in ME‐AM1 genome. One such novel gene is identified with 75 peptides, lacks homolog in other methylobacteria but has glycosyl transferase and lipopolysaccharide biosynthesis protein domains, indicating its potential role in outer membrane synthesis. Many novel genes are present only in ME‐AM1 among methylobacteria. Distant homologs of these genes in unrelated taxonomic classes and low GC‐content of few genes suggest lateral gene transfer as a potential mode of their origin. Annotations of methylotrophy related genes were also improved by the discovery of a short gene in methylotrophy gene island and redefining a gene important for pyrroquinoline quinone synthesis, essential for methylotrophy. The combined use of proteogenomics and rigorous bioinformatics analysis greatly enhanced the annotation of protein‐coding genes in model methylotroph ME‐AM1 genome.